Contemporary cultural researches on knowledge sharing - Dong, Hai; Hussain, Farookh; Chang, Elizabeth (IEEE, 2007)
Knowledge sharing, as an essential component in the field of knowledge management research, attracts increasing researchers into this discipline. Current researches on KS can be categorized as two independent views ? exploring from technical perspective or from cultural perspective. From technical perspective, researchers studied multiple methodologies implementing KS; from cultural perspective, scholars studied social issues which influence the style and the performance of KS. In this paper, we propose to compare and contrast the contemporary cultural researches on knowledge sharing from multiple perspectives. Conclusion and future work are made in the final section.